The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Comparison of Six Data Cleaning Methods for Determining Repetitive Head Impact Exposure in Youth Tackle Football - Samantha DeAngelo; Adam Culiver; Enora Le Flao; Nick Shoaf; Durshil Doshi; Ryan Tracy; Nii-Ayi Aryeetey; Anna Quatrale; Carly Smith; Jianing Ma; Jeff Pan; Jingzhen Yang; et al. (Annals of Biomedical Engineering, 2026)
Purpose Instrumented mouthguards (iMGs) are commonly used to quantify head acceleration event (HAE) exposure, but accurate interpretation requires rigorous data cleaning methods. This study compared six data cleaning methods for determining HAE rates and magnitudes, as well as cleaning method validity compared to the 5 th method video verification in youth tackle football. Methods Fifty athletes (ages 8-12) wore Impact Monitoring Mouthguards during games across one season. Six data cleaning methods were applied to HAEs, including uncleaned data, time-windowing, proprietary classification algorithms, video verification, and combinations thereof. Impact rate, peak linear acceleration (PLA), and peak rotational velocity (PRV) were compared across methods using rate ratios, and intra-class correlation coefficients (ICCs), and non-parametric analyses. Results Data cleaning methods significantly influenced HAE rate but had minimal effect on magnitude. The uncleaned dataset produced the highest HAE rate (67.75 per athlete exposure), while the most stringent method (i.e., time-windowed, proprietary algorithm-classified, video-verified data) yielded the lowest (0.70 per athlete exposure). Although the time-windowed, proprietary algorithm-classified data demonstrated high specificity (0.96), it demonstrated low sensitivity (0.37) and positive predictive value (0.39) when compared to video-verified data. Differences in PLA across methods were not significant; only one significant difference in PRV was observed. Conclusions These findings highlight the impact of data cleaning on HAE quantification in youth tackle football. Although video verification remains best practice, it is resource intensive. Time-windowed, algorithm-classified data may serve as an efficient proxy in similar cohorts, though researchers should recognize its limitations. Findings support the need for standardized data cleaning methods and transparent reporting to ensure accurate and comparable HAE exposure estimates.

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

A decision support tool for rubble stabilization on coral reefs - Shu Kiu Leung; Tania M. Kenyon; Laurie J. Raymundo; Helen E. Fox; Nathan Cook; Kailash Cook; Alasdair J. Edwards; Eric E. Fisher; Arnaud J.T. Brival; Freda E. Nicholson; Robin W.L. Philippo; Andrew C.F. Taylor; et al. (Journal of Environmental Management, 2025)

The pluralistic natural capital values of a tropical city - Adrienne Grêt-Regamey; Justine Saunders; Peter Edwards; Daniel Richards; Jahson I. Alemu; Natasha Bhatia; Roman Carrasco; Zuzana Drillet; Tze Kwan Fung; Yan Feng Leon Gaw; Wanggi Jaung; Andrea Law; et al. (Ecosystem Services, 2025)

Sex Differences in Head Acceleration Events in Law Enforcement Corrections Cadets - Carly R. Smith; Enora Le Flao; Samantha N. DeAngleo; Jeffrey J. Wing; Nathan A. Edwards; James A. Onate; Joshua A. Hagen; Scott Paur; Joshua Walters; Jaclyn B. Caccese (Annals of Biomedical Engineering, 2025)
Purpose Law enforcement cadets (LECs) undergo subject control technique training that may expose them to repetitive head impacts recorded as head acceleration events (HAEs) using instrumented mouthguards. Prior research suggests that sex and/or gender differences in HAE frequency and magnitude vary by sport. This study aimed to examine sex differences in HAE exposure among LECs during training. Methods We collected HAEs from 82 civilian LECs (16 females, mean age = 30 ± 9 years) using instrumented mouthguards. We compared peak linear acceleration (PLA) and peak rotational velocity (PRV) of HAEs > 5 g between sexes using a mixed-effects linear model, with sex and cohort as fixed-effect predictors and a random intercept for subject to account for repeated HAEs within individuals. Additionally, we assessed sex differences in the number of HAEs per athlete exposure using a negative binomial regression controlling for cohort. Results PLA was lower in female than male cadets (e.g., median PLA: females = 10.9 g, males = 12.3 g, p Conclusions Overall, sex differences in HAE frequency and magnitude during subject control technique trainings were minimal. When differences were observed, female cadets exhibited less frequent and less severe HAEs than male cadets. This finding suggests that current training practices, including sex- and/or skill-matched pairing, may effectively reduce HAE exposure risk to females.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Advancing equitable value chains for the global hydrogen economy - Kathleen M. Kennedy; Maria A. Borrero; Morgan R. Edwards; Patrick O'Rourke; Nathan E. Hultman; Kavita Surana (Energy and Climate Change, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Characterizing Head Acceleration Events in Law Enforcement Cadets During Subject Control Technique Training - Carly R. Smith; James A. Onate; Nathan A. Edwards; Joshua A. Hagen; Chris Kolba; Scott Paur; Joshua Walters; Jaclyn B. Caccese (Annals of Biomedical Engineering, 2024)
Law enforcement cadets (LECs) complete weeks of subject control technique training. Similar sport-related combat training has been shown to expose participants to head acceleration events (HAEs) that have potential to result in short- and long-term impairments. The purpose of this study was to describe the number and magnitude of HAEs in LECs throughout their training. 37 LECs (7 females; age = 30.6 ± 8.8 years; BMI = 30.0 ± 6.0) were recruited from a law enforcement organization. Participants wore instrumented mouthguards, which recorded all HAEs exceeding a resultant 5 g threshold for training sessions with the potential for HAEs. Participants completed three defensive tactics (DT) training sessions, a DT skill assessment (DTA), and three boxing sessions. Outcome measures included the number of HAEs, peak linear acceleration (PLA), and peak rotational velocity (PRV). There were 2758 true-positive HAEs recorded across the duration of the study. Boxing sessions accounted for 63.7% of all true-positive HAEs, while DT accounted for 31.4% and DTA accounted for 4.9%. Boxing sessions resulted in a higher number of HAEs per session ( F 2,28 = 48.588, p η p 2 = 0.776), and higher median PLA ( F 2,28 = 8.609, p = 0.001, η p 2 = 0.381) and median PRV ( F 2,28 = 11.297, p η p 2 = 0.447) than DT and DTA. The LECs experience a high number of HAEs, particularly during boxing sessions. Although this training is necessary for job duties, HAE monitoring may lead to modifications in training structure to improve participant safety and enhance recovery.

Longitudinal relationships between depressive symptoms, functional impairment, and physical activity in later late life - Lisa Y. Xiong; Madeline Wood Alexander; Hugo Cogo-Moreira; Che-Yuan Wu; Michael Eid; Nathan Herrmann; Damien Gallagher; Jodi D. Edwards; Krista L. Lanctôt; Susan Marzolini; David A. Bennett; Jennifer S. Rabin; et al. (GeroScience, 2024)

Temporal and spatial drivers of the structure of macroinvertebrate assemblages associated with Laminaria hyperborea detritus in the northeast Atlantic - Adam Gouraguine; Dan A. Smale; Arwyn Edwards; Nathan G. King; Mathilde Jackson-Bué; Sean Kelly; Hannah S. Earp; Pippa J. Moore (Marine Environmental Research, 2024)

Quantification of age-related changes in the structure and mechanical function of skin with multiscale imaging - Alan E. Woessner; Nathan J. Witt; Jake D. Jones; Edward A. Sander; Kyle P. Quinn (GeroScience, 2024)
The mechanical properties of skin change during aging but the relationships between structure and mechanical function remain poorly understood. Previous work has shown that young skin exhibits a substantial decrease in tissue volume, a large macro-scale Poisson’s ratio, and an increase in micro-scale collagen fiber alignment during mechanical stretch. In this study, label-free multiphoton microscopy was used to quantify how the microstructure and fiber kinematics of aged mouse skin affect its mechanical function. In an unloaded state, aged skin was found to have less collagen alignment and more non-enzymatic collagen fiber crosslinks. Skin samples were then loaded in uniaxial tension and aged skin exhibited a lower mechanical stiffness compared to young skin. Aged tissue also demonstrated less volume reduction and a lower macro-scale Poisson’s ratio at 10% uniaxial strain, but not at 20% strain. The magnitude of 3D fiber realignment in the direction of loading was not different between age groups, and the amount of realignment in young and aged skin was less than expected based on theoretical fiber kinematics affine to the local deformation. These findings provide key insights on how the collagen fiber microstructure changes with age, and how those changes affect the mechanical function of skin, findings which may help guide wound healing or anti-aging treatments.

Photogrammetry: A New Tool for Fungi? - Edward Dearberg; Nathan Smith (Fungal Biology Reviews, 2024)

SARS-CoV and SARS-CoV-2 display limited neuronal infection and lack the ability to transmit within synaptically connected axons in stem cell–derived human neurons - Jasmina M. Luczo; Sarah J. Edwards; Katie Ardipradja; Willy W. Suen; Gough G. Au; Glenn A. Marsh; Nathan Godde; Christina L. Rootes; John Bingham; Vinod Sundaramoorthy (Journal of NeuroVirology, 2024)
Sarbecoviruses such as SARS and SARS-CoV-2 have been responsible for two major outbreaks in humans, the latter resulting in a global pandemic. While sarbecoviruses primarily cause an acute respiratory infection, they have been shown to infect the nervous system. However, mechanisms of sarbecovirus neuroinvasion and neuropathogenesis remain unclear. In this study, we examined the infectivity and trans-synaptic transmission potential of the sarbecoviruses SARS and SARS-CoV-2 in human stem cell–derived neural model systems. We demonstrated limited ability of sarbecoviruses to infect and replicate in human stem cell–derived neurons. Furthermore, we demonstrated an inability of sarbecoviruses to transmit between synaptically connected human stem cell–derived neurons. Finally, we determined an absence of SARS-CoV-2 infection in olfactory neurons in experimentally infected ferrets. Collectively, this study indicates that sarbecoviruses exhibit low potential to infect human stem cell–derived neurons, lack an ability to infect ferret olfactory neurons, and lack an inbuilt molecular mechanism to utilise retrograde axonal trafficking and trans-synaptic transmission to spread within the human nervous system.

Temperature Thresholds for Leaf Damage from Two Extreme Freeze Events (2018 and 2021) Near the Northern Range Limit of Black Mangroves (Avicennia germinans) in Southeastern North America - Simen Kaalstad; Michael J. Osland; Donna J. Devlin; C. Edward Proffitt; Laura C. Feher; Anna R. Armitage; Richard H. Day; Kathleen M. Swanson; Gordon H. Anderson; Brigid Berger; Just Cebrian; Karen L. Cummins; et al. (Estuaries and Coasts, 2024)

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Vulnerability to climate change of managed stocks in the California Current large marine ecosystem - Michelle M. McClure; Melissa A. Haltuch; Ellen Willis-Norton; David D. Huff; Elliott L. Hazen; Lisa G. Crozier; Michael G. Jacox; Mark W. Nelson; Kelly S. Andrews; Lewis A.K. Barnett; Aaron M. Berger; Sabrina Beyer; et al. (Frontiers in Marine Science, 2023)
Introduction Understanding how abundance, productivity and distribution of individual species may respond to climate change is a critical first step towards anticipating alterations in marine ecosystem structure and function, as well as developing strategies to adapt to the full range of potential changes. Methods This study applies the NOAA (National Oceanic and Atmospheric Administration) Fisheries Climate Vulnerability Assessment method to 64 federally-managed species in the California Current Large Marine Ecosystem to assess their vulnerability to climate change, where vulnerability is a function of a species’ exposure to environmental change and its biological sensitivity to a set of environmental conditions, which includes components of its resiliency and adaptive capacity to respond to these new conditions. Results Overall, two-thirds of the species were judged to have Moderate or greater vulnerability to climate change, and only one species was anticipated to have a positive response. Species classified as Highly or Very Highly vulnerable share one or more characteristics including: 1) having complex life histories that utilize a wide range of freshwater and marine habitats; 2) having habitat specialization, particularly for areas that are likely to experience increased hypoxia; 3) having long lifespans and low population growth rates; and/or 4) being of high commercial value combined with impacts from non-climate stressors such as anthropogenic habitat degradation. Species with Low or Moderate vulnerability are either habitat generalists, occupy deep-water habitats or are highly mobile and likely to shift their ranges. Discussion As climate-related changes intensify, this work provides key information for both scientists and managers as they address the long-term sustainability of fisheries in the region. This information can inform near-term advice for prioritizing species-level data collection and research on climate impacts, help managers to determine when and where a precautionary approach might be warranted, in harvest or other management decisions, and help identify habitats or life history stages that might be especially effective to protect or restore.

A National Status Report on United States Coral Reefs Based on 2012–2018 Data From National Oceanic and Atmospheric Administration’s National Coral Reef Monitoring Program - Erica K. Towle; E. Caroline Donovan; Heath Kelsey; Mary E. Allen; Hannah Barkley; Jeremiah Blondeau; Russell E. Brainard; Annie Carew; Courtney S. Couch; Maria K. Dillard; C. Mark Eakin; Kimberly Edwards; et al. (Frontiers in Marine Science, 2022)
National Oceanic and Atmospheric Administration’s Coral Reef Conservation Program supports the National Coral Reef Monitoring Program (NCRMP) in the United States Pacific, Atlantic, Caribbean, and Gulf of Mexico. NCRMP conducts standardized observations of biological, climatic, and socioeconomic indicators across American Samoa, Guam, the Main Hawaiian Islands, the Northwestern Hawaiian Islands, the Northern Mariana Islands, the Pacific Remote Islands, Florida, the Flower Garden Banks, Puerto Rico, and the United States Virgin Islands. NCRMP provides periodic, national-level assessments of the status of United States coral reef ecosystems and communities connected to them. In 2014, NCRMP partnered with the University of Maryland Center for Environmental Science on an unprecedented collaboration between federal and jurisdictional/state agencies, academia, and non-governmental organizations to synthesize NCRMP data into a reporting format designed to be accessible and relevant to the public and policy makers. The process involved multi-year data analyses of key benthic, fish, and climate indicators. In populated jurisdictions, socioeconomic data were integrated to assess public support for management actions, participation in pro-environmental behaviors, and awareness of threats to coral reefs. Jurisdictions were scored using a report-card scale (0–100%) by establishing references for each indicator using best-available historical data or expert opinion where historical data did not exist or were not statistically comparable. Despite overall ecosystem scores of Fair for all combined Atlantic (70%) and Pacific (74%) jurisdictions, the current trend is downward with a majority of United States coral reefs declining and vulnerable to further degradation. Remote, uninhabited reefs had an advantage with respect to reef fish population scores, i.e., Flower Garden Banks (85%) and Pacific Remote Islands (93%), when compared to populated location scores, i.e., Puerto Rico (63%) and Main Hawaiian Islands (66%). All coral reefs are highly impacted by climate change, and climate impacts were more pronounced than expected on remote reefs, i.e., the Northwestern Hawaiian Islands (58%). Presenting results in a report-card style facilitates communication to the public and policy makers, and provides a useful mechanism to garner support for management actions such as expanding protected areas; enforcing existing regulations; increasing climate change education; reducing land-based sources of pollution; and other actions to improve the trajectory of coral reef ecosystem conditions.

A Brief Educational Intervention Enhances Basic Cancer Literacy Among Kentucky Middle and High School Students - Lauren Hudson; Kerrigan M. Samons; Haley E. Dicken; Chris Prichard; L. Todd Weiss; Jean Edward; Robin C. Vanderpool; Nathan L. Vanderford (Journal of Cancer Education, 2021)
Kentucky experiences the highest overall cancer incidence and mortality rates in the USA with the greatest burden in the eastern, Appalachian region of the state. Cancer disparities in Kentucky are driven in part by poor health behaviors, poverty, lack of health care access, low education levels, and low health literacy. Individuals with inadequate health literacy are less likely to participate in preventive measures such as obtaining screenings and making healthy lifestyle choices, thus increasing their chances of developing and dying from cancer. By increasing cancer literacy among youth and adults, it may be possible to decrease cancer disparities across Kentucky. This study aimed to establish connections with middle and high schools in Kentucky that would facilitate pilot implementation of a brief cancer education intervention and assessment of cancer health literacy among these student populations. A baseline pretest cancer literacy survey consisting of 10 items was given to 349 participants, followed by the delivery of a cancer education presentation. Immediately following the presentation, participants were given a posttest with identical items to the pretest. Participants were primarily Caucasian (89.4%), female (68.7%), and in 10th through 12th grade (80.5%). Significant ( p < 0.0001) increases in both average and median percent of correctly marked items were observed between the pretest and posttest (average, pretest = 56% versus posttest = 85%; median, pretest = 60% versus posttest = 90%). The scores for all individual items increased after the brief intervention. The results demonstrated a significant increase in cancer literacy levels immediately after the pilot educational intervention. We suggest that it may be possible to improve cancer literacy rates in Kentucky by integrating cancer education into middle and high school science and/or health education curricula. This could ultimately drive changes in behaviors that may help lower cancer incidence and mortality rates. Plans for future interventional studies measuring long-term cancer knowledge retention and resultant behavioral changes among middle and high school students as well as the feasibility of integrating cancer education into middle and high school curricula are also discussed.

Radiation Oncology Online: Quality, Strategies, and Disparities - Edward Christopher Dee; Nathan H. Varady (Journal of Cancer Education, 2020)

Integrated Risk Assessment for the Blue Economy - Emma E. Hodgson; Timothy E. Essington; Jameal F. Samhouri; Edward H. Allison; Nathan J. Bennett; Ann Bostrom; Alison C. Cullen; Stephen Kasperski; Phillip S. Levin; Melissa R. Poe (Frontiers in Marine Science, 2019)

DNA of diverse adenoviruses detected in Cameroonian rodent and shrew species - Joseph Diffo; Valantine Ngum Ndze; Nkom Felix Ntumvi; Jean-Michel Takuo; Moctar M. M. Mouiche; Ubald Tamoufe; Julius Nwobegahay; Matthew LeBreton; Amethyst Gillis; Bradley S. Schneider; Joseph M. Fair; Corina Monagin; et al. (Archives of Virology, 2019)

Toxicological effects of chemical constituents from Piper against the environmental burden Aedes aegypti Liston and their impact on non-target toxicity evaluation against biomonitoring aquatic insects - Prabhakaran Vasantha-Srinivasan; Annamalai Thanigaivel; Edward-Sam Edwin; Athirstam Ponsankar; Sengottayan Senthil-Nathan; Selvaraj Selin-Rani; Kandaswamy Kalaivani; Wayne B. Hunter; Veeramuthu Duraipandiyan; Naif Abdullah Al-Dhabi (Environmental Science and Pollution Research, 2018)

Acute toxicity of chemical pesticides and plant-derived essential oil on the behavior and development of earthworms, Eudrilus eugeniae (Kinberg) and Eisenia fetida (Savigny) - Prabhakaran Vasantha-Srinivasan; Sengottayan Senthil-Nathan; Athirstam Ponsankar; Annamalai Thanigaivel; Muthiah Chellappandian; Edward-Sam Edwin; Selvaraj Selin-Rani; Kandaswamy Kalaivani; Wayne B. Hunter; Veeramuthu Duraipandiyan; Naif Abdullah Al-Dhabi (Environmental Science and Pollution Research, 2018)

Development of an eco-friendly mosquitocidal agent from Alangium salvifolium against the dengue vector Aedes aegypti and its biosafety on the aquatic predator - Annamalai Thanigaivel; Prabhakaran Vasantha-Srinivasan; Edward-Sam Edwin; Athirstam Ponsankar; Selvaraj Selin-Rani; Muthiah Chellappandian; Kandaswamy Kalaivani; Sengottayan Senthil-Nathan; Giovanni Benelli (Environmental Science and Pollution Research, 2018)

Toxicological effects of Sphaeranthus indicus Linn. (Asteraceae) leaf essential oil against human disease vectors, Culex quinquefasciatus Say and Aedes aegypti Linn., and impacts on a beneficial mosquito predator - Muthiah Chellappandian; Annamalai Thanigaivel; Prabhakaran Vasantha-Srinivasan; Edward-Sam Edwin; Athirstam Ponsankar; Selvaraj Selin-Rani; Kandaswamy Kalaivani; Sengottayan Senthil-Nathan; Giovanni Benelli (Environmental Science and Pollution Research, 2018)

Environmental Stewardship: A Conceptual Review and Analytical Framework - Nathan J. Bennett; Tara S. Whitty; Elena Finkbeiner; Jeremy Pittman; Hannah Bassett; Stefan Gelcich; Edward H. Allison (Environmental Management, 2018)

Asymmetric responses of primary productivity to precipitation extremes: A synthesis of grassland precipitation manipulation experiments - Kevin R. Wilcox; Zheng Shi; Laureano A. Gherardi; Nathan P. Lemoine; Sally E. Koerner; David L. Hoover; Edward Bork; Kerry M. Byrne; James Cahill; Scott L. Collins; Sarah Evans; Anna K. Gilgen; et al. (Global Change Biology, 2017)
Climatic changes are altering Earth's hydrological cycle, resulting in altered precipitation amounts, increased interannual variability of precipitation, and more frequent extreme precipitation events. These trends will likely continue into the future, having substantial impacts on net primary productivity ( NPP ) and associated ecosystem services such as food production and carbon sequestration. Frequently, experimental manipulations of precipitation have linked altered precipitation regimes to changes in NPP . Yet, findings have been diverse and substantial uncertainty still surrounds generalities describing patterns of ecosystem sensitivity to altered precipitation. Additionally, we do not know whether previously observed correlations between NPP and precipitation remain accurate when precipitation changes become extreme. We synthesized results from 83 case studies of experimental precipitation manipulations in grasslands worldwide. We used meta‐analytical techniques to search for generalities and asymmetries of aboveground NPP ( ANPP ) and belowground NPP ( BNPP ) responses to both the direction and magnitude of precipitation change. Sensitivity (i.e., productivity response standardized by the amount of precipitation change) of BNPP was similar under precipitation additions and reductions, but ANPP was more sensitive to precipitation additions than reductions; this was especially evident in drier ecosystems. Additionally, overall relationships between the magnitude of productivity responses and the magnitude of precipitation change were saturating in form. The saturating form of this relationship was likely driven by ANPP responses to very extreme precipitation increases, although there were limited studies imposing extreme precipitation change, and there was considerable variation among experiments. This highlights the importance of incorporating gradients of manipulations, ranging from extreme drought to extreme precipitation increases into future climate change experiments. Additionally, policy and land management decisions related to global change scenarios should consider how ANPP and BNPP responses may differ, and that ecosystem responses to extreme events might not be predicted from relationships found under moderate environmental changes.

Diversity and Inclusion in Conservation: A Proposal for a Marine Diversity Network - Nicola S. Smith; Isabelle M. Côté; Lourdes Martinez-Estevez; Edward J. Hind-Ozan; Angela L. Quiros; Nathan Johnson; Stephanie J. Green; Leslie Cornick; David Shiffman; Luis Malpica-Cruz; Allison Gleason Besch; Nikita Shiel-Rolle (Frontiers in Marine Science, 2017)

A conceptual framework for analyzing deltas as coupled social–ecological systems: an example from the Amazon River Delta - Eduardo S. Brondizio; Nathan D. Vogt; Andressa V. Mansur; Edward J. Anthony; Sandra Costa; Scott Hetrick (Sustainability Science, 2016)

Identification of milling and baking quality QTL in multiple soft wheat mapping populations - Antonio Cabrera; Mary Guttieri; Nathan Smith; Edward Souza; Anne Sturbaum; Duc Hua; Carl Griffey; Marla Barnett; Paul Murphy; Herb Ohm; Jim Uphaus; Mark Sorrells; et al. (Theoretical and Applied Genetics, 2015)

The novel mu-opioid antagonist, GSK1521498, reduces ethanol consumption in C57BL/6J mice - Tamzin L. Ripley; Sandra Sanchez-Roige; Edward T. Bullmore; Manolo Mugnaini; Kay Maltby; Sam R. Miller; David R. Wille; Pradeep Nathan; David N. Stephens (Psychopharmacology, 2015)

Morphological Effects Induced In Vitro by Propranolol on Human Erythrocytes - Mario Suwalsky; Pablo Zambrano; Fernando Villena; Marcela Manrique-Moreno; María José Gallardo; Malgorzata Jemiola-Rzeminska; Kazimierz Strzalka; Ana María Edwards; Sigrid Mennickent; Nathan Dukes (The Journal of Membrane Biology, 2015)

The opioid receptor pharmacology of GSK1521498 compared to other ligands with differential effects on compulsive reward-related behaviours - Eamonn Kelly; Stuart J. Mundell; Anna Sava; Adelheid L. Roth; Antonio Felici; Kay Maltby; Pradeep J. Nathan; Edward T. Bullmore; Graeme Henderson (Psychopharmacology, 2015)

Neuroendocrine and sympathetic responses to an orexin receptor antagonist, SB-649868, and Alprazolam following insulin-induced hypoglycemia in humans - Ameera X. Patel; Sam R. Miller; Pradeep J. Nathan; Ponmani Kanakaraj; Antonella Napolitano; Philip Lawrence; Annelize Koch; Edward T. Bullmore (Psychopharmacology, 2014)

Human proximity and habitat fragmentation are key drivers of the rangewide bonobo distribution - Jena R. Hickey; Janet Nackoney; Nathan P. Nibbelink; Stephen Blake; Aime Bonyenge; Sally Coxe; Jef Dupain; Maurice Emetshu; Takeshi Furuichi; Falk Grossmann; Patrick Guislain; John Hart; et al. (Biodiversity and Conservation, 2013)

Effects of mu opioid receptor antagonism on cognition in obese binge-eating individuals - Samuel R. Chamberlain; Karin Mogg; Brendan P. Bradley; Annelize Koch; Chris M. Dodds; Wenli X. Tao; Kay Maltby; Bhopinder Sarai; Antonella Napolitano; Duncan B. Richards; Edward T. Bullmore; Pradeep J. Nathan (Psychopharmacology, 2012)

In vitro cultures and regeneration of Bienertia sinuspersici (Chenopodiaceae) under increasing concentrations of sodium chloride and carbon dioxide - Josh Rosnow; Sascha Offermann; Joonho Park; Thomas W. Okita; Nathan Tarlyn; Amit Dhingra; Gerald E. Edwards (Plant Cell Reports, 2011)

Commentary: the challenge of quantifying susceptibility to drought-related crisis - Edward R. Carr; Nathan P. Kettle (Regional Environmental Change, 2009)

Climatic drivers of hemispheric asymmetry in global patterns of ant species richness - Robert R. Dunn; Donat Agosti; Alan N. Andersen; Xavier Arnan; Carsten A. Bruhl; Xim Cerdá; Aaron M. Ellison; Brian L. Fisher; Matthew C. Fitzpatrick; Heloise Gibb; Nicholas J. Gotelli; Aaron D. Gove; et al. (Ecology Letters, 2009)
Although many taxa show a latitudinal gradient in richness, the relationship between latitude and species richness is often asymmetrical between the northern and southern hemispheres. Here we examine the latitudinal pattern of species richness across 1003 local ant assemblages. We find latitudinal asymmetry, with southern hemisphere sites being more diverse than northern hemisphere sites. Most of this asymmetry could be explained statistically by differences in contemporary climate. Local ant species richness was positively associated with temperature, but negatively (although weakly) associated with temperature range and precipitation. After contemporary climate was accounted for, a modest difference in diversity between hemispheres persisted, suggesting that factors other than contemporary climate contributed to the hemispherical asymmetry. The most parsimonious explanation for this remaining asymmetry is that greater climate change since the Eocene in the northern than in the southern hemisphere has led to more extinctions in the northern hemisphere with consequent effects on local ant species richness.

Bottom‐up forcing and the decline of Steller sea lions ( Eumetopias jubatus ) in Alaska: assessing the ocean climate hypothesis - ANDREW W. TRITES; ARTHUR J. MILLER; HERBERT D. G. MASCHNER; MICHAEL A. ALEXANDER; STEVEN J. BOGRAD; JOHN A. CALDER; ANTONIETTA CAPOTONDI; KENNETH O. COYLE; EMANUELE DI LORENZO; BRUCE P. FINNEY; EDWARD J. GREGR; CHESTER E. GROSCH; et al. (Fisheries Oceanography, 2007)
Declines of Steller sea lion ( Eumetopias jubatus ) populations in the Aleutian Islands and Gulf of Alaska could be a consequence of physical oceanographic changes associated with the 1976–77 climate regime shift. Changes in ocean climate are hypothesized to have affected the quantity, quality, and accessibility of prey, which in turn may have affected the rates of birth and death of sea lions. Recent studies of the spatial and temporal variations in the ocean climate system of the North Pacific support this hypothesis. Ocean climate changes appear to have created adaptive opportunities for various species that are preyed upon by Steller sea lions at mid‐trophic levels. The east–west asymmetry of the oceanic response to climate forcing after 1976–77 is consistent with both the temporal aspect (populations decreased after the late 1970s) and the spatial aspect of the decline (western, but not eastern, sea lion populations decreased). These broad‐scale climate variations appear to be modulated by regionally sensitive biogeographic structures along the Aleutian Islands and Gulf of Alaska, which include a transition point from coastal to open‐ocean conditions at Samalga Pass westward along the Aleutian Islands. These transition points delineate distinct clusterings of different combinations of prey species, which are in turn correlated with differential population sizes and trajectories of Steller sea lions. Archaeological records spanning 4000 yr further indicate that sea lion populations have experienced major shifts in abundance in the past. Shifts in ocean climate are the most parsimonious underlying explanation for the broad suite of ecosystem changes that have been observed in the North Pacific Ocean in recent decades.

Cell Proliferation of Cultured Human Cancer Cells are Affected by the Elevated Tumor Pressures that Exist In Vivo - Gene R. DiResta; Saminathan S. Nathan; Mark W. Manoso; Jorge Casas-Ganem; Chris Wyatt; Tadaheko Kubo; Patrick J. Boland; Edward A. Athanasian; Jonathan Miodownik; Richard Gorlick; John H. Healey (Annals of Biomedical Engineering, 2005)

Preparing for Climatic Change: The Water, Salmon, and Forests of the Pacific Northwest - Philip W. Mote; Edward A. Parson; Alan F. Hamlet; William S. Keeton; Dennis Lettenmaier; Nathan Mantua; Edward L. Miles; David W. Peterson; David L. Peterson; Richard Slaughter; Amy K. Snover (Climatic Change, 2003)